IMPACT OF SOCIOECONOMIC FACTORS ON DAILY URINARY SODIUM AND POTASSIUM EXCRETION IN CHINESE FIRST GENERATION MIGRANTS IN ITALY. (June 2018) - Tavilla, R.; Rapi, S.; Rogolino, A.; Toncelli, L.; Boddi, M.; Cappuccio, F.; Galanti, G.; Modesti, P.A.
Abstract : Objective: Evidence are indicating that opportunities for appropriate treatment of risk factors are unequal at population level and ethnic minorities tend to have a higher risk for stroke than the host population. Although the reduction of sodium intake is a recognized main strategy for the prevention and control of hypertension, information regarding the effective receipt of this advice by ethnic minority groups in Europe is lacking. Study aims were to assess the level of salt and potassium consumption in first-generation Chinese migrants in Italy and to explore possible associations with blood pressure and hypertension. Design and method: Population-based, cross-sectional study. Participants were 235 first-generation Chinese migrants aged 16–59 years. Subjects provided answers to a questionnaire and anthropometry and blood pressure was recorded. They were asked to perform a 24-hour urinary collection and the relationships of 24-hour urinary sodium and potassium with blood pressure (BP) values, hypertension diagnosis (BP > 140/90 mmHg or antihypertensive drug use) and hypertension awareness was investigated with logistic regression analysis. Results: Mean (SD) daily sodium excretion was 143.6 ± 52.4 and 127.7 ± 48.9 mmol/day in men and women respectively (p < 0.01), corresponding to a dietary salt intake of 9.3 ± 3.4 and 8.3 ± 3.2 g/day respectively. Mean daily potassium excretions by gender were 33.2 ± 16.7 and 32.8 ± 14.5 mmol/day respectively (ns). Daily sodium excretion (quartiles) was positively related with hypertension diagnosis and BP values at adjusted logistic regression analyses, being not influenced by hypertension awareness or by time spent in Italy. Importantly, high education level (secondary school, college or more vs illiterate or primary school) was associated with lower daily sodium (adjusted OR 0.989; Cl95% 0.981 to 0.998) and increased potassium excretion (adjusted OR 1.037;1.007 to 1.067). Hypertension awareness was not associated with any positive behaviours or educational factors either in the general cohort or in the hypertensive group. Conclusions: Salt intake in Chinese first generation migrant workers aware of their hypertension status and frequently treated with hypertensive drugs is higher than recommended and in line with high salt intake in Italy. Potassium consumption remains low.